Analisis Kandungan Gizi Dan Daya Terima Puding Modisco III Dengan Penambahan Sari Kacang Hijau (Vigna radiata L.) - Salsabila, Haura; Junita, Dini (NASUWAKES: Jurnal Kesehatan Ilmiah, 2025)
Modisco is a liquid food high in calories and protein. Some toddlers do not like Modisco because it tastes bad and the shape is less attractive, one of the efforts that can be done by modifying the pudding with the addition of mung bean juice. Mung beans contain nutrients including: protein, fiber, healthy fats, carbohydrates and are rich in vitamins that are beneficial for the growth and development of toddlers. The aim is to determine the effect of mung bean juice addition on the nutritional content and acceptability of Modisco III pudding. This research is experimental with a completely randomized design. Data processing used ANOVA and Duncan's further test. The variables studied were organoleptic test and chemical test on Modisco pudding. The result of this research are Modisco pudding with the addition of 40 g mung bean juice is preferred in terms of aroma (3.61), flavor (3.61), and texture (3.76). The results of chemical test analysis on water content, ash content, and fiber content were highest in the addition of 30 g mung bean juice, fat content, protein content, and carbohydrate content were highest in the addition of 50 g mung bean juice. Conclusion the addition of mung bean juice has a significant effect on organoleptic properties with a significant level (p value <0.05) on aroma and taste, but has no significant effect with a significant level (p value>0.05) on color and texture. In chemical tests that have a significant effect with a significant level (p value <0.05), there are water content, ash content, fat content, protein content, fiber content, and carbohydrate content.